Network disruption detected in GB (United Kingdom) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in United Kingdom. Data sourced from CensoredPlanet, IODA.
Network Disruption Incident ID: GB-2026-0002. Severity: critical. Confidence: 70%